Preparation of Information Media About Isotonic Exercise For The Elderly Leyangan Ungaran Village - Syaifudin, Achmad; Nurhayati, Susi (Health Notions, 2017)
Arthritis diseases that contribute to joint stiffness, pain and limitations of movement ranks second largest after hypertension in elderly in Indonesia based on data Ministry of Health RI in 2016. Data Puskesmas in Leyangan Ungaran Village there are 140 elderly who become built Posyandu Lansia Leyangan working area Puskesmas Leyangan . Approximately 70% of these numbers have degenerative disease problems such as stiffness in the joints and joint pain. The purpose of this study was to identify the complaints in the joints especially the elderly knee, so that will be developed information media by providing isotonic exercise appropriate and conducted intervention in elderly with complaints on the knee joint. The method used in the first stage is cluster random sampling technique of 103 elderly, second stage with purposive sampling technique at 15 elderly given intervention of isotonic movement exercise. Data were collected using questionnaire, measurement of motion range using Goniometer measured pre and post intervention, isotonic information and training media, isotonic exercise kits exercise equipment (isotonic exercise kits). Then tested by paired test t with result of difference of range of motion on right knee (p value 0.02) big difference 4.67. There is a difference of motion range on left knee (p value 0.02) big difference of 8.00.